Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1002/rcm.417
|View full text |Cite
|
Sign up to set email alerts
|

Phosphopeptide analysis by positive and negative ion matrix‐assisted laser desorption/ionization mass spectrometry

Abstract: This article describes a simple procedure for the detection of phosphorylated peptides by comparable positive and negative ion mode matrix-assisted laser desorption/ionization mass spectrometry measurements. Based on studies with phosphorylated peptides (EAIXAAPFAK, X = pS, pT, pY) and their corresponding non-phosphorylated analogs, it was found that phosphopeptides, which are characterized by a low ionization efficiency in the positive ion mode, exhibit drastically increased signal intensities in the negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
120
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 19 publications
10
120
0
Order By: Relevance
“…In addition, threonine phosphorylation leads to increase in the ionization efficiency. This result is consistent with the previous MALDI study [9] and is in line with the fact that a phosphorylated side chain can deprotonate readily to render the negatively charged peptide, thereby increasing the ionization efficiency. In this respect, the relative ionization efficiencies were measured following the same procedures as described above for the positive-ion mode.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, threonine phosphorylation leads to increase in the ionization efficiency. This result is consistent with the previous MALDI study [9] and is in line with the fact that a phosphorylated side chain can deprotonate readily to render the negatively charged peptide, thereby increasing the ionization efficiency. In this respect, the relative ionization efficiencies were measured following the same procedures as described above for the positive-ion mode.…”
Section: Resultssupporting
confidence: 93%
“…In this method, after normalizing against the signal of suitable proteolytic peptides, the extent of phosphorylation could be determined. In addition, methods for direct measurement of the ionization efficiency changes caused by PTM on peptides were reported [1,8,9]. In these prior studies, the synthetic peptides were first quantified by weight [8] or by amino acid analysis [1] and, after comparing the LC-MS results with known quantification data, the variation in ionization efficiency caused by certain PTMs could be measured.…”
mentioning
confidence: 99%
“…Our data found that in the presence of p38 MAPK, the 21-aa C-terminal MRP-14 tryptic peptide that contains Thr 113 showed an 80-Da increase in mass, as compared with MRP-14 tryptic peptides in the absence of p38 MAPK. This is consistent with phosphorylation of this peptide, as the mass of a phosphoryl group (HPO 3 ) is 80 Da (40). Use of tandem mass spectrometry allowed us to observe the ␤-elimination, neutral loss of 98 m/z from the precursor peptide ion, which is the mass of phosphoric acid (H 3 PO 4 ) (40,41).…”
Section: Discussionsupporting
confidence: 73%
“…These results indicate that MRP-14 translocates to Triton X-100 insoluble structures at the base of lamellipodia in human neutrophils upon fMLP treatment and that the translocation is p38 MAPK dependent. the 80-Da mass addition of a phosphoryl group (HPO 3 ) (40). Analysis of peptide mass spectra showed a peak at 2177.3 m/z in samples from p38 MAPK treated and untreated MRP-14 (Fig.…”
Section: P38 Mapk Phosphorylates Thr 113 On Mrp-14mentioning
confidence: 98%
“…Major drawbacks of these methods are decreased ionization rates of phosphopeptides in complex mixtures due to suppression effects. These effects can be reduced by measuring phosphopeptides in negative ion mode as their ionization is better than in positive mode [55]. Unfortunately, negative-polarity MS/MSspectra are mostly of very poor quality.…”
Section: Localization Of Phosphorylation Sitesmentioning
confidence: 99%